It's true, it's true, it's true (Oberon modern plays., 2018)
"And there's blood pouring out of this man's throat. Because these two women are beheading him - did I not mention that?" Fringe First and Total Theatre Award- winning Breach (Tank, The Beanfield) restage the 1612 trial of Agostino Tassi for the rape of baroque painter Artemisia Gentileschi. Based on surviving court transcripts, this new play dramatises the seven-month trial that gripped Renaissance Rome, and asks how much has changed in the last four centuries. Blending myth, history and contemporary commentary, this is the story of how a woman took revenge through her art to become one of the most successful painters of her generation.